Method for converting waste into fibrous membrane and application of fibrous membrane to extraction of precious metal
By stirring and mixing the papermaking black liquid and polyamine polymer in water, hydrogen bond crosslinking reaction is carried out, and nanofiber membranes are prepared by electrospinning technology, and re-crosslinking reaction is further performed in epoxychlorohydrin solution, the In the prior art, the poor selectivity of precious metal ion adsorption and limited reusability have been achieved, and the high-efficiency, low-pollution, and reusable precious metal ion adsorption effect is achieved.
Patent Information
- Application Number
- CN202411562249.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has problems such as poor selectivity, limited reusability and organic solvents that are prone to secondary pollution in terms of precious metal ion adsorption, making it difficult to achieve efficient, low-pollution, and reusable precious metal ion adsorption.
By stirring and mixing the papermaking black liquid and polyamine polymer in water, performing hydrogen bond cross-linking reaction, a uniform spinning liquid was prepared, and nanofiber membranes were prepared by electrospinning technology, and further in epoxychlorohydrin solution Re-crosslinking reaction was performed to obtain a fiber membrane with excellent adsorption properties.
It realizes excellent ion selectivity and reusability of gold ions, and can stably adsorb and extract precious metal gold in the acid soaking liquid of electronic waste, demonstrating excellent precious metal extraction efficiency and reusability, and the raw materials come from paper waste. Low cost, simple preparation process, green and environmentally friendly, and without organic solvents.
Smart Images

Figure CN119411320A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of precious metal recovery, and in particular relates to a method for converting waste into fiber membranes and the application of fiber membranes in extracting precious metals. Background Art
[0002] At present, my country's papermaking industry mainly adopts alkaline pulping. During the pulping process, the lignin in the plants is dissolved in the waste liquid in the form of alkaline lignin to form black liquor. Its large-scale discharge not only endangers human health, but also causes serious waste of resources. Alkaline lignin faces major challenges in its modification and resource utilization due to its complex structure, low molecular weight, wide distribution and low reactivity.
[0003] In the prior art, the utilization of lignin mainly relies on organic solvent modification and cross-linking polymerization with other substances, such as the treatment methods disclosed in patent applications 202110774948.2, 201910174182.7, and 201811327706.3. The organic solvents used in the above technical solutions are difficult to handle and are prone to secondary pollution during the preparation of the adsorbent. In addition, although biomass is environmentally friendly and sustainable as an adsorbent, its adsorption capacity for precious metal ions is weak, and inorganic nanoparticles have strong ability in the adsorption of precious metal ions, but their application in industrial recycling is limited. In addition, synthetic polymers are considered ideal adsorbents due to their diverse structures and ease of modification. Among them, polyamine polymers provide abundant nitrogen atoms, which can provide active sites for metal ions. Polyacrylamide is used to prepare sewage treatment agents to adsorb heavy metals in sewage, such as patent application 202410881054.7. Polyethyleneimine modifies a kind of clay to adsorb hexavalent chromium ions, such as patent application 201410056935.1. However, although polyacrylamide and polyethyleneimine have been used in the adsorption of heavy metal ions, their regeneration ability and selectivity are still insufficient. Therefore, it is particularly important to develop membrane materials with excellent regeneration ability, high selectivity and low pollution without organic solvents to achieve efficient, low-pollution and reusable precious metal ion adsorption. Summary of the invention
[0004] The purpose of the embodiments of the present invention is to provide a method for converting waste into fiber membranes, aiming to solve the problems raised in the above-mentioned background technology.
[0005] The embodiment of the present invention is implemented as follows: a method for converting waste into fiber membranes comprises the following steps:
[0006] Adding papermaking black liquor and polyamine polymer into water, stirring and mixing, and then adding additives to carry out hydrogen bond cross-linking reaction to obtain uniform spinning solution;
[0007] The spinning solution is passed through an electrospinning device to obtain a lignin-based nanofiber film, which is then immersed in an epichlorohydrin solution for a re-crosslinking reaction and then dried at room temperature to obtain a reinforced lignin-based fiber membrane.
[0008] Preferably, the mass ratio of the papermaking black liquor, the polyamine polymer and the auxiliary agent is 2-5:1-5:0.5-3.
[0009] Preferably, the polyamine-based polymer is one or more of polyaniline, poly-p-phenylenediamine, polystyrene amine, polyphenylamine, polyacrylamide, and polyethyleneimine;
[0010] The auxiliary agent is one or more of polyvinyl pyrrolidone, polyacrylamide, carboxymethyl cellulose and polyvinyl alcohol.
[0011] Preferably, the stirring speed of the stirring and mixing is 300-1000 r / min.
[0012] Preferably, the temperature of the hydrogen bond cross-linking reaction is 15-50° C. and the time is 0.3-6.0 h.
[0013] Preferably, the electrospinning conditions are as follows: an electrostatic voltage of 15-30 kV, a receiving distance of 10-20 cm, and a propulsion speed of the spinning solution of 0.03-1 mm / min.
[0014] Preferably, the mass fraction of the epichlorohydrin solution is 0.5-5%.
[0015] Preferably, the temperature of the re-crosslinking reaction is 30-80° C., and the reaction time is 12-36 hours.
[0016] Another object of an embodiment of the present invention is to provide a fiber membrane, which is prepared by the above method.
[0017] Another purpose of an embodiment of the present invention is to provide an application of the above-mentioned fiber membrane in extracting gold ions, wherein the fiber membrane is placed in a solution containing gold ions and allowed to stand.
[0018] The method for converting waste into fiber membrane provided in the embodiment of the present invention aims at the shortcomings of traditional adsorbents such as poor selectivity, limited reusability, and easy secondary pollution caused by organic solvents. The method utilizes the alkaline lignin in papermaking black liquor to form hydrogen bonds with the amine groups of polyamine polymers through its hydroxyl groups, and at the same time utilizes the interaction between the benzene rings of the alkaline lignin molecules to reduce its surface activity, thereby forming a spinning solution with a entangled cross-linked structure, and then uses electrospinning technology to prepare a nanofiber membrane, which is immersed in an aqueous solution of epichlorohydrin, and the stability of the membrane is further improved by chemical cross-linking to prepare a fiber membrane with adsorption performance. The preparation process is carried out in the aqueous phase without the use of organic solvents.
[0019] The prepared fiber membrane exhibits excellent ion selectivity and reusability for gold ions, and can stably adsorb and extract precious metal gold in the acid leaching solution of electronic waste. Compared with the existing precious metal recovery technology, the fiber membrane of the embodiment of the present invention exhibits excellent precious metal extraction efficiency and reusability. The raw materials come from papermaking waste, the cost is low, the preparation process is simple, green and environmentally friendly, and there is no organic solvent, which provides a new green solution for precious metal recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A method for converting waste into fiber membranes and a flowchart of applying the fiber membranes to gold ion adsorption provided by an embodiment of the present invention;
[0021] Figure 2 The gold ion adsorption performance results of the lignin-based nanofiber films provided in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0023] A lignin-based nanofiber film, the preparation process of which is as follows Figure 1 As shown, the specific steps include:
[0024] The papermaking black liquor and polyamine polymer are added to distilled water, stirred for a certain period of time and then mixed, and then an additive is added to carry out hydrogen bond cross-linking and allowed to stand to obtain a uniform and transparent spinning solution, and a nanofiber film is obtained by electrostatic spinning, and then the nanofiber film is immersed in epichlorohydrin for a certain period of time to improve the stability of the nanofiber film; the prepared fiber film can be used to adsorb gold ions;
[0025] Wherein, the mass ratio of papermaking black liquor, polyamine polymer and additive is 2-5:1-5:0.5-3;
[0026] The step of adding papermaking black liquor and polyamine polymers to distilled water is preferably performed by dissolving the papermaking black liquor and polyamine polymers in water respectively and then mixing them, and the mixing method is preferably magnetic stirring;
[0027] The polyamine-based polymer is one or more of polyaniline, poly-p-phenylenediamine, polystyrene amine, polyphenylamine, polyacrylamide, and polyethyleneimine, and the auxiliary agent is one or more of polyvinyl pyrrolidone, polyacrylamide, carboxymethyl cellulose, and polyvinyl alcohol; the polyamine-based polymer is preferably polyethyleneimine, preferably used in powder form, and the weight average molecular weight of the polyethyleneimine is preferably 10,000 to 80,000, more preferably 10,000 to 50,000, and most preferably 10,000; the auxiliary agent is preferably polyvinyl alcohol, preferably used in powder form;
[0028] The temperature of the hydrogen bond cross-linking reaction is 15-50°C, preferably 20-30°C, and most preferably 24°C; the time is 0.3-6.0h, preferably 0.3-1h, and most preferably 0.4h;
[0029] The temperature of electrospinning is 15-50°C, more preferably 20-30°C, most preferably 23°C;
[0030] After spinning is completed, the embodiment of the present invention further comprises a step of drying the nanofiber film, and the drying is preferably air-drying at room temperature;
[0031] The mass fraction of epichlorohydrin solution is 0.5-5%, preferably 0.5-2%, most preferably 1%;
[0032] The temperature of the re-crosslinking reaction is 30-80°C, preferably 50-60°C, and most preferably 60°C; the time is 12-36h, preferably 20-30h, and most preferably 24h.
[0033] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0034] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0035] Example 1: A lignin-based nanofiber film, the specific preparation method of which is as follows:
[0036] (1) adding papermaking black liquor and polyethyleneimine with a weight average molecular weight of 10,000 to water, mixing them evenly by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bond crosslinking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor, polyethyleneimine and polyvinyl alcohol is 5:1:3;
[0037] (2) passing the spinning solution through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution advancing speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then drying it at room temperature;
[0038] (3) The polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film is placed in a 1% by mass epichlorohydrin aqueous solution at a temperature of 60° C. for 24 hours for re-cross-linking, and then dried at room temperature to obtain a reinforced lignin-based nanofiber film.
[0039] Example 2: A lignin-based nanofiber film, the specific preparation method of which is as follows:
[0040] (1) adding papermaking black liquor and polyethyleneimine with a weight average molecular weight of 10,000 to water, mixing them evenly by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bond crosslinking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor, polyethyleneimine and polyvinyl alcohol is 5:2:3;
[0041] (2) passing the spinning solution through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution advancing speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then drying it at room temperature;
[0042] (3) The polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film is placed in a 1% by mass epichlorohydrin aqueous solution at a temperature of 60° C. for 24 hours for re-cross-linking, and then dried at room temperature to obtain a reinforced lignin-based nanofiber film.
[0043] Example 3: A lignin-based nanofiber film, the specific preparation method of which is as follows:
[0044] (1) adding papermaking black liquor and polyethyleneimine with a weight average molecular weight of 10,000 to water, mixing them evenly by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bond crosslinking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor, polyethyleneimine and polyvinyl alcohol is 5:3:3;
[0045] (2) passing the spinning solution through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution advancing speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then drying it at room temperature;
[0046] (3) The polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film is placed in a 1% by mass epichlorohydrin aqueous solution at a temperature of 60° C. for 24 hours for re-cross-linking, and then dried at room temperature to obtain a reinforced lignin-based nanofiber film.
[0047] Example 4: A lignin-based nanofiber film, the specific preparation method of which is as follows:
[0048] (1) adding papermaking black liquor and polyethyleneimine with a weight average molecular weight of 10,000 to water, mixing them evenly by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bond crosslinking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor, polyethyleneimine and polyvinyl alcohol is 5:4:3;
[0049] (2) passing the spinning solution through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution advancing speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then drying it at room temperature;
[0050] (3) The polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film is placed in a 1% by mass epichlorohydrin aqueous solution at a temperature of 60° C. for 24 hours for re-cross-linking, and then dried at room temperature to obtain a reinforced lignin-based nanofiber film.
[0051] Example 5: A lignin-based nanofiber film, the specific preparation method of which is as follows:
[0052] (1) adding papermaking black liquor and polyethyleneimine with a weight average molecular weight of 10,000 to water, mixing them evenly by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bond crosslinking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor, polyethyleneimine and polyvinyl alcohol is 5:5:3;
[0053] (2) passing the spinning solution through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution advancing speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then drying it at room temperature;
[0054] (3) The polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film is placed in a 1% by mass epichlorohydrin aqueous solution at a temperature of 60° C. for 24 hours for re-cross-linking, and then dried at room temperature to obtain a reinforced lignin-based nanofiber film.
[0055] Comparative Example 1: A lignin-based nanofiber film, the specific preparation method of which is as follows: (without adding polyamine)
[0056] (1) adding papermaking black liquor to water, dispersing it in the water by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bonding cross-linking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor to the polyvinyl alcohol is 2:1;
[0057] (2) passing the spinning solution through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution advancing speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then drying it at room temperature;
[0058] (3) The polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film is placed in a 1% by mass epichlorohydrin aqueous solution at a temperature of 60° C. for 24 hours for re-cross-linking, and then dried at room temperature to obtain a lignin-based nanofiber film.
[0059] Comparative Example 2: A lignin-based nanofiber film, the specific preparation method of which is as follows: (without adding epichlorohydrin)
[0060] (1) adding papermaking black liquor and polyethyleneimine with a weight average molecular weight of 10,000 to water, mixing them evenly by magnetic stirring, and then adding an auxiliary agent polyvinyl alcohol to carry out hydrogen bond crosslinking at a temperature of 24° C. for 0.4 h to obtain a uniform and transparent spinning solution; the mass ratio of the papermaking black liquor, polyethyleneimine and polyvinyl alcohol is 5:3:3;
[0061] (2) The spinning solution is passed through an electrospinning device at a temperature of 23° C., an electrostatic voltage of 15 kV, a receiving distance of 10 cm, and a spinning solution propulsion speed of 0.04 mm / min to prepare a polyethyleneimine (PEI) cross-linked alkali lignin nanofiber film, and then placed at room temperature for drying to obtain a lignin-based nanofiber film.
[0062] Performance Testing:
[0063] The gold ion adsorption capacity of the lignin-based nanofiber films prepared in Examples 1-5 and Comparative Examples 1-2 was tested and compared, and the specific steps were as follows:
[0064] Seven groups of 10 ppm gold chloride solutions were prepared to simulate the actual water environment of electronic waste leachate. The lignin-based nanofiber films prepared in Examples 1-5 and Comparative Examples 1-2 were placed in the above gold chloride solutions and allowed to stand for 24 hours. Quantitative tests were performed using atomic absorption spectrophotometry. The results were as follows: Figure 2 As shown;
[0065] according to Figure 2 It can be seen from the data of Comparative Example 1 and Examples 1-5 that the lignin-based nanofiber film without the introduction of polyamine has a poor adsorption effect on gold ions, and the single lignin has a limited adsorption effect on gold ions. The introduction of polyamine can significantly improve the adsorption performance of lignin for gold ions. This is because the coordination effect occurs between the amino group and the metal ion to form a stable complex, thereby improving the adsorption effect;
[0066] according to Figure 2 It can be seen from the data of Comparative Example 2 and Examples 1-5 that after the lignin-based nanofiber film is soaked in epichlorohydrin, the adsorption capacity of the lignin-based nanofiber film for gold ions is significantly improved. Epichlorohydrin can increase the stability and durability of the material and the adsorption capacity by cross-linking with the lignin-based nanofiber film;
[0067] By comparing the data of Examples 1-3, it is found that increasing the amount of polyamine introduced is beneficial to improving the adsorption performance of the lignin-based nanofiber membrane for gold ions;
[0068] By comparing the data of Examples 3-5, it can be seen that when the amount of polyamine increases to a certain extent, it will affect its adsorption performance. Therefore, the introduction amount of polyamine polymer is a key factor in the gold ion adsorption efficiency. The optimal ratio within the range is 5:3:3 (papermaking black liquor: polyethyleneimine: polyvinyl alcohol).
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for converting waste into fiber membranes, characterized in that: The following steps are involved: Adding papermaking black liquor and polyamine polymer into water, stirring and mixing, and then adding additives to carry out hydrogen bond cross-linking to obtain a uniform spinning solution; The spinning solution is passed through an electrospinning device to obtain a lignin-based nanofiber film, which is then immersed in an epichlorohydrin solution for a re-crosslinking reaction and then dried at room temperature to obtain a reinforced lignin-based fiber membrane.
2. The method for converting waste into fiber membrane according to claim 1, characterized in that: The mass ratio of the papermaking black liquor, the polyamine polymer and the auxiliary agent is 2-5:1-5:0.5-3.
3. The method for converting waste into fiber membrane according to claim 1, characterized in that: The polyamine-based polymer is one or more of polyaniline, poly-p-phenylenediamine, polystyrene amine, polyphenylamine, polyacrylamide, and polyethyleneimine; The auxiliary agent is one or more of polyvinyl pyrrolidone, polyacrylamide, carboxymethyl cellulose and polyvinyl alcohol.
4. The method for converting waste into fiber membrane according to claim 1, characterized in that: The stirring speed of the stirring and mixing is 300-1000r / min.
5. The method for converting waste into fiber membrane according to claim 1, characterized in that: The temperature of the hydrogen bond cross-linking is 15-50° C., the time is 0.3-6.0 h, and the solvent is distilled water.
6. The method for converting waste into fiber membrane according to claim 1, characterized in that: The conditions for the electrostatic spinning are as follows: an electrostatic voltage of 15-30 kV, a receiving distance of 10-20 cm, and a propulsion speed of the spinning solution of 0.03-1 mm / min.
7. The method for converting waste into fiber membrane according to claim 1, characterized in that: The epichlorohydrin content in the epichlorohydrin solution is 0.5-5% of the distilled water solvent.
8. The method for converting waste into fiber membrane according to claim 1, characterized in that: The temperature of the re-crosslinking reaction is 30-80° C., and the reaction time is 12-36 hours.
9. A fiber membrane, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the fiber membrane as claimed in claim 9 in extracting gold ions, characterized in that: The fiber membrane is placed in a solution containing gold ions and allowed to stand.
Citation Information
Patent Citations
Polyethylene imine -attapulgite adsorbent preparation and hexavalent chromium adsorption method
CN103831089A
Lignin / cellulose-acetate-based electrostatic spinning carbon fiber and preparation method and application thereof
CN109853086A
Method for preparing carbon nanofiber through electrostatic blending of polyacrylonitrile / lignin
CN109943920A
A method and application for electrospinning self-assembly of lignin-supported zirconium hybrid materials
CN113578387B
A sewage treatment agent containing o-tert-butyl cyclohexyl acetate and preparation method thereof
CN118420080B